Validity and Factor Structure of House and Rizzo's Effectiveness Scales - Morgan, Cyril P.; Hitt, Michael A. (Academy of Management Journal, 1977)
The article discusses a study which examined the validation efforts on scales measuring dimensions of the organizational effectiveness of work units. The results showed three dimensions exhibiting a significant linear relationship to the overall work unit effectiveness. There was support for the relationship of six variables to effectiveness. For the prediction of overall work unit effectiveness only adaptability, decision delay, and information distortion and suppression contributed significantly.